2019
DOI: 10.1001/jamaophthalmol.2019.0440
|View full text |Cite|
|
Sign up to set email alerts
|

Retinal Nonperfusion Characteristics on Ultra-Widefield Angiography in Eyes With Severe Nonproliferative Diabetic Retinopathy and Proliferative Diabetic Retinopathy

Abstract: IMPORTANCE Threshold of retinal nonperfusion for the development of proliferative diabetic retinopathy (PDR) is unclear.OBJECTIVES To identify a threshold of retinal nonperfusion for the presence of retinal neovascularization and the distribution and area of retinal nonperfusion in eyes with severe nonproliferative diabetic retinopathy (NPDR), PDR, neovascularization of the optic disc (NVD), and retinal neovascularization elsewhere (NVE). DESIGN, SETTING, AND PARTICIPANTS This cross-sectional image analysis st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 22 publications
(42 reference statements)
0
65
0
1
Order By: Relevance
“…Widefield fluorescein angiography revealed that peripheral retinal nonperfusion is a common finding in eyes with DR [86]. These peripheral nonperfusion lesions have been associated with higher risks of DR progression and support the hypothesis that peripheral nonperfusion may be a useful surrogate for and potential predictor of proliferative DR [87][88][89]. Therefore, numerous researchers have explored the use of widefield OCTA to identify peripheral capillary nonperfusion [90][91][92][93].…”
Section: Peripheral Retinal Nonperfusionmentioning
confidence: 73%
“…Widefield fluorescein angiography revealed that peripheral retinal nonperfusion is a common finding in eyes with DR [86]. These peripheral nonperfusion lesions have been associated with higher risks of DR progression and support the hypothesis that peripheral nonperfusion may be a useful surrogate for and potential predictor of proliferative DR [87][88][89]. Therefore, numerous researchers have explored the use of widefield OCTA to identify peripheral capillary nonperfusion [90][91][92][93].…”
Section: Peripheral Retinal Nonperfusionmentioning
confidence: 73%
“…Baxter et al [13] demonstrated that a NP threshold size greater than 23% of the retinal image is associated with posterior segment NV. Nicholson et al [14] also suggested that at least 107.3 DA of NP are at risk of proliferative disease. This study adds the finding that the size of the NP area is also associated with the size of the NV area in PDR eyes.…”
Section: Discussionmentioning
confidence: 99%
“…UWF FA highlighted the importance of peripheral lesions in DR [11,12]. Quantitative analyses using UWF FA revealed that a larger NP area was associated with the presence of posterior NVs and NV at the disc area (NVD) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, images were analyzed and retinas graded by two independent examiners. It should be noted that greater peripheral DR lesions in UWFA have been associated with more severe DR [29][30][31] Limitations of this study were that we did not correct the peripheral warp present in UWFA. Since the most peripheral part of a UWFA image is magni ed, we evaluated retinal non-perfusion using NPI instead of evaluating absolute areas of non-perfusion.…”
Section: Discussionmentioning
confidence: 99%